Immunotherapy and Systemic Therapy in Metastatic/Recurrent Endometrial and Cervical Cancers. Issue 9 (September 2021) - Lima, J.; Ali, Z.; Banerjee, S.
Abstract: Despite advances in the treatment of gynaecological malignancies, both recurrent endometrial and cervical cancers when not amenable to localised therapy (surgery or radiotherapy), remain incurable with limited prognosis and effective treatment options. Chemotherapy remains the standard of care for women with metastatic endometrial or cervical cancers. The addition of bevacizumab to first-line chemotherapy for metastatic cervical cancer patients represents a significant step forward in improving survival. More recently, immunotherapeutic strategies targeting the PD-1/-L1 pathway have shown clinical activity in both endometrial and cervical cancers. The increased understanding of the molecular biology of these cancers is shaping target-specific treatments. Here we summarise current treatment options and results from clinical trials of immunotherapy and other targeted therapies that have already changed, or have the potential to change, clinical practice in metastatic/recurrent endometrial and cervical cancer.